Association of ZNF608 Polymorphisms With House Dust Mite‐Induced Allergic Rhinitis - Huiqin Li; Fang Gao; Xuyan Liu; Haoran Shen; Mulong Du; Lei Cheng; Huihui Zhang; Zhengdong Zhang; Meiping Lu; Rui Zheng (Clinical and Translational Allergy)
ABSTRACT Background Genetic factors contribute essentially to the pathophysiology of house dust mite (HDM)‐induced allergic rhinitis. Previous studies mainly focused on the biological pathogenesis, but the heritability remains poorly explained. Methods A genome‐wide gene association analysis (GWGAS) integrating joint‐genetic variant effects at the gene level was initially conducted on allergic rhinitis, validated by differential gene expression analysis. A weighted polygenic risk score (wPRS) was used to proxy the cumulative effect of candidate genetic variants in key genes. Gene‐set analysis and eQTL analysis were performed to explore the immunologic pathway and genetic regulation of the key gene. Results ZNF608 was identified as the key gene involving HDM‐induced allergic rhinitis risk (p = 1.23 × 10−6), which was highly expressed in nasal epithelium cells of allergic rhinitis patients (p = 0.041). Furthermore, a wPRS of five significant variants, rs6862252, rs10067299, rs10042766, rs6866116, and rs79679768 in the ZNF608, showed the cumulative effect was associated with the increased HDM‐induced allergic rhinitis risk (odds ratio [OR] = 1.40, 95% confidence interval [CI] = 1.18–1.65, p = 1.18 × 10−4), with varied effects under diverse conditions of nasal symptoms. Additionally, both rs6862252 G allele and rs10042766 T allele elevated the expression of ZNF608 involving in state and perturbation of immune cells, such as B cell, T cell, and dendritic cell, contributing to HDM‐induced allergic rhinitis. Conclusion This study highlights the key gene ZNF608 of HDM‐induced allergic rhinitis, which may lay the groundwork for risk assessment and early diagnosis of allergic rhinitis.